Reaction and deformation mechanism of a slipping-stretching landslide: Example of the Liangtianao ancient landslide, Guangxi Province, China - Youjun, Li; Hongri, Zhang; Liming, Huang; Sulian, Lan; Hongming, Li; Xuexiao, Wu (Frontiers in Earth Science, 2023)
The slipping-stretching landslide has long been recognized as a common type in landslide cases, but reactions of the landslide have rarely reported. There had been a slipping-stretching landslide reaction at Liangtianao, Guangxi Province, China, and the geological background and deformation characteristics of the case were identified by detailed geological survey and long-term monitoring. A FEM model of the case is built by GEO5 to analyze the mechanism of reaction and deformation. The results are as follows: 1) The Liangtianao landslide was a bedding rock ancient landslide, which stayed creeping state after the landslide occurred in the geological history. 2) The new sliding surface in Liangtianao landslide is basically consistent with the weak interlayers formed by ancient landslide, and the fault-type is slipping-stretching type with deformation process as: Strain at leading edge by road excavation→Leading edge instability→Middle part shear and creep→Back edge tensile. 3) Micro-geomorphology, rock mass bedding and weak interlayers are internal causes of the Liangtianao landslide reaction, while excavation unloading, rainfall are the external causes. The inclinometer indicates that the Liangtianao landslide is still highly sensitive to rainfall after landslide reaction, and rainfall may trigger a secondary landslide reaction. 4) The numerical analysis results indicate that the maintenance of passive state of anti-sliding section is highly beneficial to maintaining basic stable after the landslide reaction, and unloading only 1/20 of the sliding section make the landslide in a long-term stable state.